Role of leaf structure in resistance to powdery mildew in water melon - Zhang, Hui-Jun; Ge, Yu; Wang, Qiang; Zhang, Jian-Nong (The Indian Journal of Genetics and Plant Breeding, 2016)
Four varieties of water melon, exhibiting highly susceptible to highly resistant response to powdery mildew, were investigated for the role of wax content, stomata number, stomata size, and thickness of palisade and spongy tissues in resistance to powdery mildew.The results revealed: (1) wax content of the resistant varieties was remarkably higher than in the susceptible varieties; (2) stomata on the upper surface of leaves in the resistant varieties was significantly dense than in the susceptible ones, but stomata size in the resistant varieties was just the opposite; and (3) the layer of spongy tissue in the resistant varieties was thicker than that in the susceptible genotypes, but the layer of palisade tissue was thinner in the resistant genotypes compared to the susceptible ones. Wax content, stomata number, stomata size, and thickness of palisade and spongy tissues could serve as a reliable indicator of resistance to powdery mildew in melon.